2005
DOI: 10.1017/s0952836905007454
|View full text |Cite
|
Sign up to set email alerts
|

Ecological correlates of home‐range size in spring–summer for female roe deer (Capreolus capreolus) in a deciduous woodland

Abstract: Data on 22 radio-collared adult female roe deer Capreolus capreolus in the Chizé forest were used to test whether their home-range size was influenced by resource availability and reproductive status. As roe deer females are income breeders and invest heavily in each reproductive attempt, they should be limited by energetic constraints. Thus it was expected that: (1) heavier females should have larger home ranges; (2) that home-range size should decrease with increasing vegetation biomass; (3) home-range size … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
50
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(58 citation statements)
references
References 44 publications
6
50
0
2
Order By: Relevance
“…Several previous correlative studies have supported the idea that home ranges function to provide sufficient food resources (Tufto et al 1996;Lurz et al 2000;Saïd et al 2005) and this has been shown experimentally in bank voles, Clethrionomys glareolus (Jonsson et al 2002). In agreement with this, in our study, smaller home ranges contained a greater percentage of food plants and especially a greater relative abundance of annuals.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Several previous correlative studies have supported the idea that home ranges function to provide sufficient food resources (Tufto et al 1996;Lurz et al 2000;Saïd et al 2005) and this has been shown experimentally in bank voles, Clethrionomys glareolus (Jonsson et al 2002). In agreement with this, in our study, smaller home ranges contained a greater percentage of food plants and especially a greater relative abundance of annuals.…”
Section: Discussionsupporting
confidence: 92%
“…Intraspecific variation in home range size may be caused by many different factors, such as sex (e.g. Mikesic & Drickamer 1992;Asher et al 2004;Begg et al 2005), age (Mikesic & Drickamer 1992), reproductive effort (Tufto et al 1996;Saïd et al 2005), availability of nesting sites and cover (Tufto et al 1996;Getz et al 2005;Hayes et al 2007) and food availability (Taitt & Krebs 1981;Ims 1987;Tufto et al 1996;Jonsson et al 2002;Saïd et al 2005).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although the summer and spring of 2003 were reported to be exceptionally warm (Rebetez et al 2006), this is not a major problem; in the other study site no systematic difference in sampling period occurred between adults and young (see below). Moreover, a potential decrease in habitat quality during 2003 caused by the drought should have led to a decreasing power to detect the exploration of young roe deer because roe deer home range increases with decreasing habitat quality (Tufto et al 1996, Said et al 2005a. Visual inspection of the locations from two young (one male and one female) revealed that these animals used two distinct home ranges during our study period, making comparisons with the other animals that used only one home range more difficult to interpret; hence both individuals were discarded from further analysis.…”
Section: Data Collectionmentioning
confidence: 99%
“…Different factors have been identified to affect home range size in roe deer: habitat quality (Tufto et al 1996, Said et al 2005a, Said & SerVanty 2005, the presence of dependent young (Tufto et al 1996, Said et al 2005a), population density (VinCent et al 1995, Kjellander et al 2004) and age (StrandGaard 1972, Bideau et al 1993, VinCent et al 1995. In particular, Bideau et al (1993) found that the home range of young male roe deer was larger than that of adults.…”
mentioning
confidence: 99%